Pengaruh Persepsi Harga, Kualitas Pelayanan, dan Promosi terhadap Minat Beli Konsumen pada Kfc Batam - Mistianasari, Dita Mistianasari; Ngaliman, Ngaliman; Yanti, Sri (Zona Manajerial: Program Studi Manajemen (S1), 2021)
The purposes of this study are: (1) To determine the effect of price perception on consumer buying interest at KFC Batam. (2) To determine the effect of service quality on consumer buying interest at KFC Batam (3) To determine the effect of promotion on consumer buying interest at KFC Batam (4) To determine the effect of price perception, service quality and promotion simultaneously affect consumer buying interest at KFC Batam. The research method used in this research is a survey. This research was conducted at 10 Kentucky Fried Chicken (KFC) Fast Food Restaurants in Batam City. The ten locations taken are 10 locations with the busiest consumers in Batam City based on internal data from KFC Batam City. The sample of this study was 100 respondents who were divided into 10 KFC branches in Batam City. The results of this study indicate that (1) Partially Price Perception has a positive and significant effect on buying interest in KFC in Batam City (0.00 > 0.05). (2) Partially Quality of service has a positive and significant effect on buying interest in KFC in the City. Batam (0.011 > 0.05). (3) Partially Promotion has a positive and significant effect on buying interest in KFC in Batam City (0.000 > 0.05). (4) Simultaneously price perception, service quality, promotion simultaneously have a positive effect and significant to the buying interest of KFC in Batam City (0.000 > 0.05).